When Is Choice Empowering? Examining Gender Differences in Varietal Adoption through Case Studies from Sub-Saharan Africa - Polar, Vivian; Ashby, Jacqueline A.; Thiele, Graham; Tufan, Hale Ann (MDPI, 2021)
This paper examines the question of what makes choice empowering and critiques prevalent approaches to empowerment focused narrowly on agency as the ability of individuals to make their own free choices and act independently. The implications of a narrow focus on agency are illustrated with the examples of technology choice in agriculture, specifically choices involved in the adoption of improved plant varieties. This example elucidates the limits of individual agency and permits an analysis of how choices may be structured to be either empowering or disempowering, with examples from specific plant breeding cases. In view of the importance given to equitable choice of technology for closing the gender gap in agricultural productivity and sustainability, the paper explores what practical steps can be taken towards a balanced approach to empowerment. An approach to designing a new plant variety by constructing choice differently is illustrated, using information on gender relations. The paper derives lessons from the plant breeding cases to inform other kinds of interventions, so that work on how choices are defined is given as much importance for empowerment as creating the option to choose. Agents who exercise power over rules and resources can either reproduce the status quo or innovate; thus, a balanced approach to empowerment requires careful analysis of the elements of choice.